Green extraction method of cellulose fibers from oil palm empty fruit bunches - Maha Mohammad Al-Rajabi,; Teow, Yeit Haan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Oil palm empty fruit bunches (OPEFB) is one of the major biomass wastes produced from palm oil extraction process. Due to high cellulose content in OPEFB, the cellulose fibers in OPEFB can be extracted and utilized in versatile applications as a sustainable process technology development. Among multiple pre-treatment processes, chemical pre-treatment is most efficient for the removal of hemicellulose and lignin in extracting high purity cellulose from lignocellulosic biomass. With the undisputed importance of green technology for the progress of our society, it is vital to engage and leverage on green technology in chemical pre-treatment method for extracting cellulose from OPEFB. The objective of this study is to explore a green extraction method for cellulose from OPEFB using low concentration and eco-friendly chemicals. Fourier transform infrared spectroscopy and field emission scanning electron microscope was used to detect the functional groups and to observe the surface morphology of OPEFB, de-waxed OPEFB fibers, delignified OPEFB fibers, acid hydrolyzed OPEFB fibers, and OPEFB extracted cellulose fibers at different stages in confirming the removal of wax, lignin, and hemicellulose from OPEFB extracted cellulose at the end of the extraction process. Crystallinity index increased from 28% for OPEFB to 72% for the OPEFB extracted cellulose, affirms the degradation of OPEFB’s amorphous structure and transforms into higher crystallinity structure. This work has successfully developed a green extraction method for OPEFB cellulose fibers as part of sustainable process technology which would promote the utilization of lignocellulosic agricultural waste from palm oil industry in various applications.